2017
DOI: 10.4236/oalib.1103402
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Intervening Effect of Political Stability on the Relationship between Performance Contracting and Measurement, and Public Service Delivery in Kenya

Abstract: The performance of public agencies is influenced and affected by many factors, both internal and external. The internal factors are in many cases controllable, while external factors tend to fall outside the control of public sector managers. Moreover, the effect may serve to ameliorate performance or intervene to weaken performance and thereby adversely affect delivery of services. This paper explored the intervening effect of political stability, an external factor, on the relationship between performance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The government avers however that political stability is the advantage that Malaysia rides on, and that foreign direct investment comes to the country precisely because of this stability. This is backed by many theories and empirical studies, as mentioned in the first section of this paper, as well as by companies stating explicitly that political stability is the main reason that attracted them to Malaysia (Ndubai et al, 2017, [13]).…”
Section: Alesina Et Al (1992: 2) [9]mentioning
confidence: 76%
“…The government avers however that political stability is the advantage that Malaysia rides on, and that foreign direct investment comes to the country precisely because of this stability. This is backed by many theories and empirical studies, as mentioned in the first section of this paper, as well as by companies stating explicitly that political stability is the main reason that attracted them to Malaysia (Ndubai et al, 2017, [13]).…”
Section: Alesina Et Al (1992: 2) [9]mentioning
confidence: 76%
“…However, there were obstacles, such as insufficient resources, a lack of training, and a lack of official awards. Ndubai et al (2016) investigated factors influencing public service delivery in Kenya. The study found that performance contracting improved service delivery to the public by 73.6 percent (Veronesi, 2021;Seok et al, 2021;Al Harthy, 2021;Al-Mudhafar, 2021: Obenge, et al, 2014Opata, 2016 andLynch, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the State Corporations Advisory Committee (2019), 2 out of 5 are dissatisfied with public services. This is besides instituting a transparent customer feedback and grievance redress procedure, the introduction of performance management systems and service charters in the public sector whose challenges are influenced by the history, administration and culture of managing performances within the public sector (Ndubai, 2017). The civil service is faced with the challenge of poor and deteriorating performance, which acts as a stumbling block to realization of sustainable economic growth.…”
Section: Statement Of the Problemmentioning
confidence: 99%